Construction of a Bioluminescent Labelling Plasmid Vector for Bifidobacteria - Moon, Gi-Seong (Korean J Food Sci Anim Resour, 2018)
Bifidobacterium is recognized as one of the most beneficial microorganisms in our gut. Many researches on bifidobacteria have been done to understand their roles in the gut. The objective of the present study was to develop a bioluminescent labelling plasmid vector for bifidobacteria to facilitate their visualization in vitro, in situ, and in vivo. A plasmid replicon (2.0 kb) of plasmid pFI2576 previously identified from B. longum FI10564 was amplified by PCR and cloned into pUC19 plasmid vector (2.68 kb). The cloned replicon was subcloned into pTG262 (luc(+)) recombinant plasmid vector (7.4 kb) where a luciferase gene (luc(+)) from pLuc2 (8.5 kb), an Escherichia coli and lactobacilli shuttle vector, was inserted into pTG262 plasmid vector. The final recombinant DNA, pTG262::pFI2576 rep (luc(+)), was transferred into a B. catenulatum strain. This recombinant strain showed 3,024 relative luminescence units at OD(600) value of 0.352. Thus, this recombinant plasmid construct can be broadly used for labelling bifidobacteria.